Hydroclimate projections for Panama in the late 21st Century - Fábrega, José; Nakaegawa, Tosiyuki; Pinzón, Reinhardt; Nakayama, Keisuke; Arakawa, Osamu (My University, 2013)
This work analyzes hydroclimate projections in Panama toward the end of the 21st century by employing the MRIAGCM3.1 model. Understanding the impact of climate change on water resources is fundamental for a number of economic activities in Panama (i.e. Panama Canal operation, hydropower generation, and agriculture). Therefore, it is important to assess hydroclimatic impacts in specific basins using reliable Atmospheric Global Circulation Models (AGCMs) validated against actual field data. A 20-km mesh experiment was developed by using time-sliced analysis for current (1979–2002) and future (2075–2099) periods. Uncertainty in climate projections were addressed by completing 60-km mesh AGCM ensemble experiments at three additional lower boundary conditions. Four regions in Panama were selected for detailed analysis: from east to west, Bocas del Toro, Veraguas, Panama Canal and Darien. Projections show significant precipitation increases from May and July to December for all regions except Bocas del Toro. In this region, a decrease in precipitation is expected between April and August. Total runoff for all regions followed the changes in precipitation as expected. Due to net radiation increases, projected evaporation did not appear to be affected by precipitation changes.
This work analyzes hydroclimate projections in Panama toward the end of the 21st century by employing the MRIAGCM3.1 model. Understanding the impact of climate change on water resources is fundamental for a number of economic activities in Panama (i.e. Panama Canal operation, hydropower generation, and agriculture). Therefore, it is important to assess hydroclimatic impacts in specific basins using reliable Atmospheric Global Circulation Models (AGCMs) validated against actual field data. A 20-km mesh experiment was developed by using time-sliced analysis for current (1979–2002) and future (2075–2099) periods. Uncertainty in climate projections were addressed by completing 60-km mesh AGCM ensemble experiments at three additional lower boundary conditions. Four regions in Panama were selected for detailed analysis: from east to west, Bocas del Toro, Veraguas, Panama Canal and Darien. Projections show significant precipitation increases from May and July to December for all regions except Bocas del Toro. In this region, a decrease in precipitation is expected between April and August. Total runoff for all regions followed the changes in precipitation as expected. Due to net radiation increases, projected evaporation did not appear to be affected by precipitation changes.
Keywords: Panama; hydroclimate projection; MRIAGCM3.1; precipitation; evaporation; total runoff; Panama; hydroclimate projection; MRIAGCM3.1; precipitation; evaporation; total runoff